Professional Conduct Rules and Confidential Information versus Solicitor-Client Privilege: Lawyers' Disputes and the Use of Client Information - Mercer, Malcolm (Canadian Bar Review, 2013)
Disclaimer: This summary was generated by AI based on the content of the source document.